Reducing Alarm Fatigue in Maternal Monitoring on Labor and Delivery: A Commentary on Deimplementation in Obstetrics - Kern-Goldberger, Adina R.; Hamm, Rebecca F.; Raghuraman, Nandini; Srinivas, Sindhu K. (American Journal of Perinatology, 2022)
Hospital labor and delivery floors frequently operate like intensive care units (ICUs)—with continuous data feeds pouring into central monitoring stations against a background of blaring alarms. Yet the majority of obstetric patients are healthy and do not require ICU-level care. Despite limited organizational recommendations guiding the frequency of vital sign measurement, continuous pulse oximetry is used widely for laboring patients. There is also no evidence that morbidity prevention is linked to specific frequencies of vital sign monitoring in low-risk patients. In fact, studies examining the performance of maternal early warnings systems based on vital signs suggest that these may not reliably provide actionable information regarding maternal physiologic status. Furthermore, it is very possible that intrapartum maternal overmonitoring can impact care negatively by generating alarm fatigue, causing providers to miss actual abnormal vital signs that may precede morbidity.Key Points
Keywords: alarm fatigue; deimplementation; implementation science; maternal monitoring; labor and delivery; patient safety